UMPSA showcases ResQ Solar Emergency Power Station at National Preparedness Month 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
JERANTUT, 13 October 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) strengthened its role as an institution that supports innovative green energy efforts by introducing the ResQ Solar Emergency Power Station in conjunction with the National Preparedness Month (BKN) 2025 Celebration held at Padang FA Jerantut, Pahang. This innovative product was created by Senior Engineer from the Centre for Property Development and Management (PPPH), Ts. Haji Mohd Nurakla Mohd Azlan; Associate Professor Ts. Dr. Amir Abdul Razak from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA); and Associate Professor Dr. Abdul Syukor Abd Razak from the Faculty of Civil Engineering Technology (FTKA).